Understanding and treating fear of pain - Asmundson, Gordon J. G.; Vlaeyen, Johan W. S. (Johan Wolfgang Silvain), 1957-; Crombez, Geert (Oxford University Press, 2004)
People who suffer from chronic pain are typically found to be more anxious and fearful of pain than those who do not. Studies have shown how the pain itself can serve as a mechanism through which chronic pain is maintained over time, through a chain of behavioural processes. This is the first book to detail the theory, research and clinically applicable issues of a condition - fear of pain - one known to cause significant suffering and functionaldisability.